Formação e trabalho docente: um estudo com professores de ensino médio - Francisco, Eduardo (2010)
This empirical research examined the work of teachers and its current disarrangement in contemporary society. It also tried to relate it to the present cultural and educational crisis. The main goal was to analyze different ways of teacher s adaptation and resistance to the rising control over their work. By taking that into consideration, this research tried to explain how teachers see their own education and career as well as whether they are aware of this control or not. Moreover, this study tried to identify the value assigned by teachers to the political participation in their labor union. The analysis is based upon the social theoretical tradition of the Critical Theory of Society. The concepts of education, resistance, adaptation and social control were studied as well. In order to carry out this investigation a questionnaire and an attitude scale, elaborated according to Likert method, were applied to 125 teachers of public secondary schools of Sao Paulo. To analyze the collected information, the attitude scale was subdivided in four subscales: education, valuation, control and politics/union. Then, several statistics analysis was undertaken: descriptive statistics, correlation among the four subscales, correlation between the general scale and the group of subscales, and finally the analysis of hypothesis tests. The results showed that teachers have a tendency to assign high value to their education and career. Besides that, they are aware of the rising control over their work and, yet, they assign high value to the political organization which defends their career. In short it was possible to confirm the initial hypotheses: teachers have a tendency to show more resistance than adaptation to the current rising control over their work. It´s important to highlight the fact that teachers graduated from public universities showed higher resistance tendencies to the control over their work than the ones graduated from private institutions